The Personality of Isa/Jose in the Novel Saq al-Bamboo by Saud Alsanousi: A Study of Sigmund Freud's Literary Psychology - Dinda Nurlatifah; Dedi Supriadi; Mohammad Rosyid Ridho (Hasanuddin University, 2025)
The novel Saq al-Bamboo by Saud Alsanousi presents various psychological issues that reflect the dynamics of human behavior. The psychological turmoil experienced by the main character in the novel demonstrates that the surrounding environment can be a significant factor infliensing the formation of an individual’s personality. This study aims to examine: (1) the personality structure of the main character, and (2) the factors that influence the main character’s personality in Saq al-Bamboo. This research employs a qualitative method with a literary psychology approach based on Sigmund Freud’s psychoanalytic theory. The data source for this research in the novel Saq al-Bamboo by Saud Alsanousi. Data collection techniques involve reading and note-taking methods, while data analysis is conducted using descriptive analysis by describing all classified data. The findings of the study indicate that the personality structure of the main character consists of the id, ego, and superego, which interact and form a unified whole in the character’s life situations. The factors influencing the main character's personality are divided into two categories: (1) internal factors, including heredity and self-identity, attention and affection, as well as resilience and perseverance; and (2) external factors, including the influence of family environment, culture and society, and discriminatory treatment experienced by the main character.